Acquired port‐wine stains in six pediatric patients. Issue 1 (20th October 2019) - Stephens, Michael R.; Putterman, Elana; Yan, Albert C.; Castelo‐Soccio, Leslie; Perman, Marissa J.
Abstract: Background/objectives: Port‐wine stains, also known as capillary malformations, are due to dermal vascular ectasia and dilation and are most commonly congenital; however, acquired port‐wine stains (APWS) developing later in life have been noted in the literature, most commonly in the context of trauma. Methods/results: This case series presents 6 pediatric patients with APWS who first developed lesions between ages 3 and 11 years in the absence of a traumatic or other etiologic trigger. Conclusions: The epidemiology, clinical features, and treatment response of these patients are compared to what has been previously described in other cases in the literature.